Comparison of physicochemical and antibacterial properties of stingless bee honey (Trigona species) and tualang honey in Malaysia - Fatimah Ibrahim Jibril
Problem statement: High level of health risk due to increasing number of resistant pathogenic microbe leads to a search for alternative remedy. In Malaysia, there is insufficient data on the compositional properties and antibacterial activity of stingless bee honey (Meliponini) from Trigona species. The stingless bee honey is readily available and utilized in Malaysia as a natural remedy, and there is increasing awareness of stingless bee keeping (Meliponiculture) with a greater demand of the stingless bee honey due to the gradual recognition of its importance. Therefore study on the compositional properties and antibacterial activity of stingless bee honey from Trigona species is highly needed which should be compared with studies of a wellrecognized honey such as the Malaysian tualang honey tKoompassia excelsa). Methodology: Five fresh honey samples were randomly collected directly from farms across Malaysia, four of which were stingless bee honey samples, Trigona thorasica Kelantan (TtK), Trigona itama Kelantan (TiK), Trigona thorasica Terengganu (TtU), and Trigona itama Terengganu (TiU). The fifth honey was a non-stingless bee honey, Tualang honey (TuA). For the antibacterial screening, six bacteria sample were used including Staphylococcus aureus, Staphylococcus ep ide rmidis , Streptococcus pyogenes, Escherichia coli, Salmonella Typhi, and Klebsiella pneumoniae. Proximate compositional properties of the honey uch as pH, moisture content, ash content, electric conductivity, color intensity, and hydroxymethylfurfural (HMF), were identified using various analytical methods. Gas chromatography-mass spectrometry technique (GCMS) was used to determine the bioactive compound in e Jrmrey samples. The antibacterial activity of the honey was determined by agar well diffusion technique. Non-peroxide activity test was determined by catalase treatment and hydrogen peroxide test was conducted using amplex red reagent kit. Microbroth dilution technique was used for the determination of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the honey samples. Result: All the obtained values from physicochemical analysis were within the normal standard range. Higher moisture content values, lower pH, and ash content were recorded from the stingless bee honey as compared with the values of tualang honey. Different color codes were obtained, and HMF was only detected in two of the stingless bee honey samples that were collected from the same farm. Several organic compounds were identified and grouped into various classes of compounds uch as acids, carbohydrates, esters, aromatic compounds, aldehydes, and ketones. Acids and esters are the main compounds of all the stingless bee honey, while carbohydrates are the major group of compounds in tualang honey. The honey samples showed clear zones of inhibition against all the tested organisms, indicating a positive antibacterial activity. Larger zones of inhibition were recorded from the agar well diffusion method for the stingless bee honey as compared with the moderate activity of Tualang honey. There was no significant difference between the antibacterial activity of catalasetreated honey and catalase-untreated honey for the entire honey samples. All the recorded zones of inhibition demonstrated a non-hydrogen peroxide activity in both the stingless bee honey and tualang honey. The stingless bee honey samples were negative to the hydrogen peroxide test which confirms the absence or an in ignificant amount of hydrogen peroxide in the Malaysian stingless bee honey samples used. Meanwhile, the test indicated the presence of hydrogen peroxide in tualang honey which has no effect on the antibacterial activity of the honey a shown by the nonhydrogen peroxide activity test. The minimum inhibitory concentration and minimum bactericidal concentration values of the stingless bee honey samples were obtained at lower percentage concentrations for all the test organisms as compared with the values of tualang honey. Conclusion: The stingless bee honey samples have higher moisture content and acidity than the tualang honey. As compared with the tualang honey, the stingless bee honey is rich in organic acids which contribute to the property of the honey. La tly, the study reveal greater antibacterial activity from the Malaysian stingless bee honey as compared with the activity of Tualang honey. Therefore the Malaysian stingless bee honey shows promising potential as an antibacterial agent.